Saliva pH testing in predicting dental caries in children aged 7–10 years - Fudali-Walczak, Magdalena; Raba, Grzegorz; Obłoza, Beata (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Dental caries remains the most widespread disease of the masticatory system. According to WHO and FDI reports, the epidemic of dental caries has not been reduced. In Poland, dental caries prevalence among children remains high and is among the highest in Europe. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aims: 1. to assess the values of saliva pH testing used as a screening test for assessing the risk of dental caries in children. 2. to assess the correlation of saliva pH testing with the condition of the oral cavity, expressed by means of the DMF index. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material, methods: The research group consisted of 128 children aged 7–10 years. The research involved: 1. a check-up performed by means of basic dental instruments. 2. assessment of patient’s saliva pH by means of a litmus paper. On the basis of the check-ups performed, the DMF index was established for each patient. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: 1. Presence of dental caries – 75.8%. 2. Percentage of children with missing teeth – 18%. 3. Percentage of children undergoing treatment – 79.7%. 4. Correlation value of the DMF index and saliva pH: 0.693; - 0.730 (p=0.000). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: 1. The condition of health of the oral cavity in children aged 7–10 years is bad. 76% have been diagnosed with dental caries, 18% of children have at least one missing tooth. 2. Saliva pH testing is highly correlated with active dental caries, thus it can be a useful self-control test for assessing the condition of health of the oral cavity in children.